Morphological specializations of mosquito CO 2 -sensing olfactory receptor neurons - Shadi Charara; Jonathan Choy; Kalyani Cauwenberghs; Pawel Vijayakumar; Renny Ng; Keun-Young Kim; Shih-Che Weng; Omar S. Akbari; Mark H. Ellisman; Scott A. Rifkin; Chih-Ying Su (Proceedings of the National Academy of Sciences, 2025)
Hematophagous mosquitoes use CO 2 as a key arousal signal that gates behavioral responses to host-derived cues. In Aedes aegypti , CO 2 is detected by olfactory receptor neurons (ORNs) housed in the sensory hairs (sensilla) on the maxillary palp. While the molecular mechanism and behavioral significance of CO 2 sensing have been well studied in mosquitoes, the nanoscale three-dimensional structures of their CO 2 -sensing ORNs and associated cells have remained unclear. Using serial block-face scanning electron microscopy, we characterize the CO 2 -sensing cpA neuron and its odor-sensitive neighbors, cpB and cpC, within the capitate sensilla of A. aegypti. Notably, cpA neurons are significantly larger, with an outer dendritic surface area 8 to 12 times greater than that of cpB and cpC neurons. This expanded CO 2 -sensing surface arises from its unique architecture, consisting of numerous flattened dendritic sheets folded into intricate lamellae. In contrast, cpB and cpC dendrites exhibit sparse, narrow cylindrical branches. Moreover, the cpA axon displays a prominent pearls-on-a-string morphology, with numerous mitochondria-rich, nonsynaptic varicosities connected by thin cables. Remarkably, a glial cell and an auxiliary cell together ensheathe the cpA soma but not cpB or cpC, suggesting a specialized role in supporting cpA function. Compared to Drosophila CO 2 -sensitive ORNs, a larger portion of the cpA outer dendrite is embedded within the sensillum cuticle, potentially improving access to environmental CO 2 . These findings reveal key morphological specializations of cpA neurons, thereby advancing our understanding of mosquito sensory biology and laying the groundwork for future studies on the molecular basis and functional ramifications of these anatomical adaptations.